Perbaikan Tata Letak Fasilitas dengan Pendekatan Simulasi dan Evolutionary Algorithm pada Segmen I PT X - Aloysius Fung Elnino Senatra; I Gede Agus Widyadana (Jurnal Titra, 2022)
PT X is a circuit breaker company that produces various types of products. There are several production segments and each segment are used to produce one product type. PT X has conducted an evaluation of the facility layout in segment I, and found the need to improve the facility layout. Shortcomings of the current layout are the arrangement of several facilities, which located outside of the available area for segment I. The arrangement of new production layout, however, should not reduce production output. Production facility re-layout is costly; therefore, simulation is used to analyze the proposed layout. Simulation approach is used to compare the initial layout against the proposed layout. The simulation model was built using Promodel 10 software, with a simulation time of 22.5 hours and replicated for 25 times. The proposed layout is derived using an evolutionary algorithm method, with adjustment in respect to some constraints from the initial layout. The proposed layout can answer the needs of segment I, because there are no facilities that exceed the specified area and result in more products in a day than the initial model.